Effect of Uncontrolled Type-II Diabetes Mellitus and Its Duration on Nerve Conduction Parameters in Adult Sudanese Patients in Khartoum State - Awad, Kamal M.; Abdalgadir, Ahmed A.; Osman, Asim A.; Saeed, Mohammed E.; Osman, Makawi A. A. (Sudan Journal of Medical Sciences, 2024)
Background: Peripheral neuropathy is a serious complication of diabetes, which has socioeconomic consequences as well as a reduced quality of life. Early neuropathic process recognition and management could alter its course and considerably reduce the associated morbidity and mortality. This study determines the effect of long-term glycemic control on diabetic peripheral neuropathy in people with type 2 diabetes (T2DM). Methods: A hospital-based study was carried out at the National Centre of Neurosciences and Ibrahim Malik Hospital in Khartoum. All individuals who were older than 18 years and have had T2DM for less than 10 years were recruited. Using accepted techniques, the BMI, HbA1c level, and nerve conduction studies (NCS) were measured. Data were analyzed using the Statistical Package for Social Sciences (SPSS), version 25.0 software. P-value ≤ 0.05 was considered significant. Results: Of the 95 patients with T2DM, 52 were male patients. Our findings showed that as the duration of diabetes increased, the sensory velocity reduced from 64.07 ± 3.22 to 54.00 ± 5.34 and the motor nerve from 63.39 ± 2.38 to 53.87 ± 2.08 (P = 0.05, P = 0.003, respectively). Additionally, with increased duration of diabetes, a significant decrease was seen in both motor nerve amplitude from 8.79 ± 3.11 to 6.94 ± 1.84 (P = 0.05) and sensory nerve amplitude from 25.71 ± 5.70 to 19.51 ± 6.51 (P = 0.003). Also, all parameters of NCS (velocity and amplitude) decreased when Hb A1c was >6 – sensory velocity from 63.96 ± 2.36 to 55.49 ± 2.43 (P = 0.03) and motor velocity from 63.00 ± 2.59 to 51.44 ± 1.66 (P = 0.02). And sensory amplitude decreased from 26.91 ± 1.26 to 20.85 ± 2.1 (P = 0.05), while motor amplitude decreased from 6.88 ± 3.55 to 6.61 ± 3.29 (P = 0.05). Additionally, there is a substantial (P = 0.05) correlation between sensory and motor amplitudes and the BMI. Conclusion: High BMI and poorly controlled (high HbA1c) long-term diabetes had a negative impact on all nerve conduction study parameters.